Using synthetic jet generators in the systems of control of separated flows of turbomachines - Богданов, Микола Юрійович; Кірчу, Федір Іванович (Technology audit and production reserves, 2015)
The article presents the features of the use of pulse-periodic systems, which are presented in the form of generators of synthetic jets and can be used to eliminate flow separation of blade rows of turbomachines. It is known that the control system of separated flows characterized by greater efficiency in the modes of operation of stages of turbomachines that are close to resonance. Therefore, ensuring the flexibility of the control system of separated flows and the possibility of its adjustment under certain operating conditions of stages of turbomachines, greatly expand the range of effectiveness of the latter. Such flexibility of the control system of separated flow can be achieved by using a moving element, which is used as a vibration exciter. With moving parts can configure the system to the required frequency range, the moving element can also play the role of a diagnostic element of the system. It should be noted that the integral separated wake on the stages of axial turbomachines has a requirement for control method for the presence of feedback, which in turn needs a shaping procedure and settings. Adjusting the natural frequency of the control system of separated flows will provide expansion of its range of effective work, as well as increase the efficiency of stages of turbomachines in general. The study results can be used for the selection of configuration of moving parts of repetitively pulsed systems.